(untitled) (Palimpsesto, 2023)
The work uses the writings and interviews of Martínez de Hoz and his economic team to reconstruct the explanations they gave with a view to the central objectives of their management. To carry out this objective the article will be divided as follows. There will be a first section aimed at addressing the question of the objectives and goals of producing structural change, essentially economic and classist. A second section, to point out the limits that were imposed on Martínez de Hoz’s management. A third section, will be used to analyze changes in the labor market. The fourth one, will delve into the distributional breakdown, the fall in wages and the increase in inequalities. The fifth section will have as its central theme, the prohibition of collective agreements and the union reform carried out. Finally, the work will close with some conclusions in this regard.